IDENTIFIKASI KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V DI SDN 30 MATARAM TAHUN AJARAN 2020/2021 - Gendis Shoha Zakhia; Muhammad Tahir; Baiq Niswatul Khair (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
In this 21st century era, there is a huge change accoured in the world called industrial revolution 4.0. In this era, a High Order Thinking Skill (HOTS) of fifth grade students at 30 Mataram Elementary School year 2020/2021 in order to be able to compete and participate directly in this industrial revolution 4.0. This study focusing on 6 aspects of critical thinking, such as focus, reason, inference, situation, clarity and overview. This study used descriptive qualitative approach. The samples of this study were fifth grade students at 30 Mataram Elementary School. Data collecting methods used were test, observation, interviews and documentation. The result of this study showed that 25,71% of students' got result that were categorized as very good, 40,00% of students' result were categorized as good, 22,86% of students' result were categorized as fair and the rest of 11,43% were categorized as poor.